Faktor Determinan Minat Wirausaha Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Gorontalo - Herwin Mopangga (TRIKONOMIKA, 2014)
This research aims to describe the actual condition of the entrepreneurial student at the Faculty of Economics and Business, Gorontalo State University (FEB-UNG), identifying the determinant factor of student entrepreneurial intention and to formulate alternative ways to improve the entrepreneurial intention. Use qualitative descriptive method, primary data obtained by 50 selected respondent, and secondary data from student division of FEB-UNG office. Research concludes, first, it is generally, student entrepreneurial intention still relatively low, evidenced by the lack of FEB students become entrepreneur, low involvement in training/workshop and seminar about entrepreneurship inside or outside of campus as well as the lack of number of business plan that competed in Program of Student Creativity (PKM). Second, relatively low of entreprenurial intention is highly determined by the lack supporting of parents and family who works as civil servant or private employees, public perception and also entrepreneurial learning atmosphere and facilities that have to be acces inside of campus. Third, the solutions offered is multiplied the frequence of entrepreneurial practices, carried out of learning contextual periodically, provide the entrepreneurial facilities, business incubator program, business plan writing contest, budget allocation and entrepreneurial network integrated with local stakeholder.